SISTEM INFORMASI PELAYANAN KESEHATAN REKAM MEDIS PASIEN MENGGUNAKAN FRAMEWORK LARAVEL - Tristiyanto Tristiyanto; Sasqia Yovita Dewi; Rizky Prabowo (Jurnal Pepadun, 2021)
The medical record is a patient's medical record during the examination. Information on medical records is needed as a reference for further action. Medical records consist of conventional medical records and electronic medical records. Medical records in several health facilities are still stored on paper media. Manually storing medical record data has a disadvantage, namely that it is very difficult to find previous patient medical record data, even though it has been separated according to category, the data search process still takes a long time. The use of databases in information systems makes it easy to exchange data and search for medical records. This information system is expected to provide benefits in use, fast in service, and safe in data storage. The research methodology uses the Research and Development (R&D) method. The R&D stage consists of concept, analysis and architecture, development, leverage and validation. Medical Record Health Service Information System was built to assist and facilitate medical record services in health facilities. The Medical Record Health Service Information System provides access rights to four users, namely: superadmin, admin, medical personnel, and patients. Each user has a different function. Types of medical records are emergency medical records, inpatient medical records, outpatient medical records, and laboratory medical records.